Application of photogrammetry reconstruction for hyperthermia quality control measurements. (September 2022) - Drizdal, Tomas; Paulides, Margarethus M.; Sumser, Kemal; Vrba, David; Malena, Lukas; Vrba, Jan; Fiser, Ondrej; van Rhoon, Gerard C.
Highlights: Photogrammetry method has a potential to improve hyperthermia measurement setup reconstruction. Better agreement between measured and predicted SAR using photogrammetry method can be obtained. Photogrammetry method can provide a tool towards quantitative hyperthermia applicators validation. Abstract: Purpose: Hyperthermia is a cancer treatment in which the target region is heated to temperatures of 40–44 °C usually applying external electromagnetic field sources. The behavior of the hyperthermia applicators (antennas) in clinical practice should be periodically checked with phantom experiments to verify the applicator's performance over time. The purpose of this study was to investigate the application of photogrammetry reconstructions of 3D applicator position in these quality control procedure measurements. Methods: Photogrammetry reconstruction was applied at superficial hyperthermia scenario using the Lucite cone applicator (LCA) and phased-array heating in the head and neck region using the HYPERcollar3D. Wire-frame models of the entire measurement setups were created from multiple-view images and used for recreation of the setup inside 3D electromagnetic field simulation software. We evaluated applicator relation ( R a ) between measured and simulated absolute specific absorption rate (SAR) for manually created and photogrammetry reconstructed simulation setups. Results: We found a displacement of 7.9 mm for the LCA and 8.2 mm for the HYPERcollar3D setups when comparing manually created and photogrammetry reconstructed applicator models placements. R a improved from 1.24 to 1.18 for the LCA and from 1.17 to 1.07 for the HYPERcollar3D when using photogrammetry reconstructed simulation setups. Conclusion: Photogrammetry reconstruction technique holds promise to improve measurement setup reconstruction and agreement between measured and simulated absolute SAR.